Educação ambiental: práticas no espaço escolar e uma análise bibliográfica reflexiva - COSTA, Kercy Cristina de Nazaré (2020)
This theme raised the following issues: What is the content of research on environmental education in Brazil? How does the process of political and educational awareness in this theme occur? How does the formation of the subject involved in the socio-environmental action take place? The general objective of this paper is to analyze the importance of discourses and research on environmental education, emphasizing ongoing reflections and research, through the state of the art. In addition, it is also intended to know through the specific objectives, such as: promote an educational policy on environmental education through school practice and provide an environmental education for citizen training. Our methodology is based on qualitative bibliographic research. And finally, we will present a discussion based on dialogues between the authors and affirmatives on the theme, confronted in old and current actions among the theme of environmental education and the social transformation of the environment.